2021
DOI: 10.3390/ma14216564
|View full text |Cite
|
Sign up to set email alerts
|

Application of Operational Load Monitoring System for Fatigue Estimation of Main Landing Gear Attachment Frame of an Aircraft

Abstract: In this paper, we present an approach to fatigue estimation of a Main Landing Gear (MLG) attachment frame due to vertical landing forces based on Operational Loads Monitoring (OLM) system records. In particular, the impact of different phases of landing and on ground operations and fatigue wear of the MLG frame is analyzed. The main functionality of the developed OLM system is the individual assessment of fatigue of the main landing gear node structure for Su-22UM3K aircraft due to standard and Touch-And-Go (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…1) Full-scale fatigue tests (FSFT) encompassing the whole structure physically being tested with methods, such as strain gauges mounted to localise and quantify strain (Dziendzikowski et al, 2021).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…1) Full-scale fatigue tests (FSFT) encompassing the whole structure physically being tested with methods, such as strain gauges mounted to localise and quantify strain (Dziendzikowski et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Instead, basing the replacement of the LG on the amount and severity of loads encountered can be accomplished by collecting data with the use of sensors, thereby allowing for the quantification and classification of the factors causing imminent fatigue failure. Currently, such an ideology is approached by a form of OLM systems, which consists of strain gauges placed on military aircraft (Hunt and Hebden, 2001;Dziendzikowski et al, 2021) wherein the strain output is transformed into digital signals that are thereby converted into stress histories, resulting in a loading sequence. Nevertheless, this method of fatigue assessment is inadequate for structural damage detection, by virtue of leaving out "a factor of two to three in fatigue life to be gained if damage could be monitored more adequately" (Staszewski and Boller, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible as many structures are subjected to a limited number of load types in their operating environment. For example, Dziendzikowski et al [7] identified only 8 load cases of main landing gear attachment frame of an aircraft (as there is a limited number of parameters set during touchdown). The following paper presents an idea where the data for SHM/OLM process is acquired using Digital Image Correlation (DIC).…”
Section: Introductionmentioning
confidence: 99%
“…The microscale effects may be important when considering potential failure mechanisms in composite materials (microcracks, delamination, etc.). The presented approach of time-efficient determination of stresses in inclusions and matrix within composites could be used in the future, for example, in structural health monitoring (SHM) of modern structures [ 39 , 40 ], and especially in the variant of SHM known as Operational Load Monitoring processes (OLM, fatigue tracking) [ 41 , 42 , 43 ]. In OLM the amount and characteristics of load cycles that a structure endured in its operational environment are measured and registered.…”
Section: Introductionmentioning
confidence: 99%